PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. SARANA RESWARA ABADI - Sri Puji Astuti; Wiwik Rachmarwi (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
To analyze the effect of discipline and work environment on employee performance PT. Sarana Reswara Abadi. This research is a causal associative research with a quantitative approach. This research is a causal associative research with a quantitative approach. The population and sample of this research are employees of PT. Reswara Abadi ingredients are taken based on the Slovin formula with a random sampling technique. Data collection using a questionnaire that has been tested for validity and reliability. The data analysis technique was performed using partially and simultaneous regression analysis. The Result discipline and work environment have a positive and significant effect on the performance of the employees of PT. Sarana Reswara Abadi, either partially and simultaneous.